2008
DOI: 10.1352/0047-6765(2008)46[12:dciqol]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Does Choice Influence Quality of Life for People With Mild Intellectual Disabilities?

Abstract: Consumer choice is a key concept in developmental disability intervention, but relatively little quantitative research has focused on the relationship between choice and quality of life. This study used data from Washington state's Division of Developmental Disabilities 2002 National Core Indicators study (Human Services Research Institute, 2001a, 2001b) to examine the relationship between choice and 3 quality-of-life indicators: community inclusion, rights, and opportunities for relationships. Consumers (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 9 publications
1
37
0
1
Order By: Relevance
“…While the relationship between choice and better quality of life has been well-documented (e.g. NeelyBarnes, Marcenko, & Weber, 2008) it is of little value if an individual's expressed choices are then ignored, which was a relatively common experience for the participants in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…While the relationship between choice and better quality of life has been well-documented (e.g. NeelyBarnes, Marcenko, & Weber, 2008) it is of little value if an individual's expressed choices are then ignored, which was a relatively common experience for the participants in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…Choice-making is an important component of self-determination, which is linked to several adult outcomes, including residential setting, quality of life, and better quality employment (Lachapelle et al, 2005;Neely-Barnes et al, 2008;Shogren et al, 2015;Wehmeyer & Bolding, 1999;Wehmeyer & Palmer, 2003). Employment was chosen as the dependent variable in this study, as in previous research (Martoell et al, 2008;Wehmeyer & Palmer, 2003), but choice-making and employment have an unclear causal relationship and future research is needed to better understand the relationship.…”
Section: Choice-makingmentioning
confidence: 99%
“…That is, their choices should affect their lives to the highest degree possible [8]. As Neely-Barnes et al [22] suggested, this should result in an improved quality of life, enhanced happiness, or determination of the best courses of action when confronted with a problem. The more opportunities there are for indi-viduals to make meaningful choices, the more control they will experience [21]; and it is believed that this increased control will be crucial in achieving self-selected goals.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between choice making and increased quality of life remains equivocal [14]. As Neely-Barnes et al [22] noted, choice making per se is not an indicator of improved quality of life. The extent to which choices are provided is important but the critical variable is the extent to which these choices are encouraged, respected, and supported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation